Carbothermal Synthesis of Nitrogen-Doped Graphene Composites for Energy Conversion and Storage Devices - Mi, Hongwei; Yang, Xiaodan; Hu, Jun; Zhang, Qianling; Liu, Jianhong (Frontiers in Chemistry, 2018)
Metal oxides and carbonaceous composites are both promising materials for electrochemical energy conversion and storage devices, such as secondary rechargeable batteries, fuel cells and electrochemical capacitors. In this study, Fe3O4 nanoparticles wrapped in nitrogen-doped (N-doped) graphene nanosheets (Fe3O4@G) were fabricated by a facile one-step carbothermal reduction method derived from Fe2O3 and liquid-polyacrylonitrile (LPAN). The unique two-dimensional structure of N-doped graphene nanosheets, can not only accommodate the volume changes during lithium intercalation/extraction processes and suppress the particles aggregation but also act as an electronically conductive matrix to improve the electrochemical performance of Fe3O4 anode, especially the rate capability. What's more, by etching Fe3O4@G to remove the iron-based oxide template, porous N-doped graphene composites (NGCs) were prepared and presented abundant pore structure with high specific surface area, delivering a specific capacitance of 172 F·g−1 at 0.5 A·g−1. In this way, Fe2O3 was both template and activator to adjust the pore size of graphene. And the effect of specific surface area and pore size tuned by the Fe2O3 activator were also revealed.